Unlocking circular economy and green innovation pathways for sustainable biofuel: a global bibliometric analysis with insights from Indonesia’s B40 transition - Harjanti, Susy; Prabowo, Harjanto; Rahim, Rano Kartono (Frontiers in Sustainability, 2025)
The global transition toward sustainable energy systems requires biofuel production pathways that embrace circular economy principles and green innovation strategies. While circular economy and green innovation are widely referenced in the biofuel literature, research remains fragmented, lacking a comprehensive mapping of their intersection and practical insights for policy and industry. This study conducts a global bibliometric analysis to systematically map research trends, thematic structures, and collaboration networks at the intersection of circular economy and green innovation within the biofuel sector. Using data from Scopus and Web of Science (2020–2025), the analysis employs VOSviewer and Biblioshiny to examine publication growth, thematic clusters, temporal evolution, influential authors, and country-level collaborations. The findings reveal distinct thematic clusters linking circular economy strategies, waste management, green technology adoption, and sustainability policy. Despite this growing body of research, significant knowledge gaps remain, including limited integration of circular economy practices, fragmented technological innovation pathways, and underdeveloped policy frameworks. Collaboration network analysis highlights uneven global research connectivity, underscoring opportunities for stronger thematic integration and international cooperation. By offering a global mapping of these trends and gaps, this study provides strategic insights to guide the development of more circular and innovative biofuel systems. With specific reference to Indonesia’s B40 transition policy as an illustrative context, the analysis highlights actionable pathways to support sustainability, decarbonization, and market access goals. The results offer a critical evidence base for policymakers, industry leaders, and researchers to prioritize investments, strengthen collaboration networks, and design coherent strategies for advancing sustainable biofuel production.